Lumbar Stenosis: A Recent Update by Review of Literature - Seung Yeop Lee; Tae-Hwan Kim; Jae Keun Oh; Seung Jin Lee; Moon Soo Park (Asian Spine Journal, 2015)
Degeneration of the intervertebral disc results in initial relative instability, hypermobility, and hypertrophy of the facet joints, particularly at the superior articular process. This finally leads to a reduction of the spinal canal dimensions and compression of the neural elements, which can result in neurogenic intermittent claudication caused by venous congestion and arterial hypertension around nerve roots. Most patients with symptomatic lumbar stenosis had neurogenic intermittent claudication with the risk of a fall. However, although the physical findings and clinical symptoms in lumbar stenosis are not acute, the radiographic findings are comparatively severe. Magnetic resonance imaging is a noninvasive and good method for evaluation of lumbar stenosis. Though there are very few studies pertaining to the natural progression of lumbar spinal stenosis, symptoms of spinal stenosis usually respond favorably to non-operative management. In patients who fail to respond to non-operative management, surgical treatments such as decompression or decompression with spinal fusion are required. Restoration of a normal pelvic tilt after lumbar fusion correlates to a good clinical outcome.